Advancing catalytic fast pyrolysis through integrated multiscale modeling and experimentation: Challenges, progress, and perspectives. Issue 4 (26th April 2018) - Ciesielski, Peter N.; Pecha, M. Brennan; Bharadwaj, Vivek S.; Mukarakate, Calvin; Leong, G. Jeremy; Kappes, Branden; Crowley, Michael F.; Kim, Seonah; Foust, Thomas D.; Nimlos, Mark R.
Abstract : Catalytic fast pyrolysis (CFP) is a conversion process that integrates rapid thermochemical depolymerization of solid feedstocks with catalytic transformation to yield small molecules for fuel and chemical products. This process is well‐suited for the conversion of nonfossil feedstocks such as biomass and waste plastics, and thereby holds great potential for the production of renewable commodities. In spite of many technological developments in various aspects of CFP achieved over decades of research, this technology has yet to attain commercial success for the production of fuels and chemicals from renewable feedstocks. Effective CFP processes require careful coordination of chemical and physical phenomena that span very large length and time scales. A broad spectrum of scientific progress in both pyrolysis and catalytic upgrading has provided the foundation for successful deployment of CFP, although additional progress in process‐scale integration is yet required for commercial realization. Modeling and simulation tools provide an important framework wherein the CFP technologies by be better understood and evaluated from a holistic perspective. Here we provide a detailed description of the multiscale phenomena underlying CFP, describe challenges and associated technical progress, and suggest strategies for an integrated approach to advance this technology toward commercialization. This article is categorized under: Bioenergy > Systems and Infrastructure Bioenergy > Science and Materials Abstract : Catalytic fast pyrolysis is a thermochemical conversion process that holds great potential for production of fuels and chemicals from renewable feedstocks. The process requires careful coordination of complex chemical and physical phenomena that span many length and time scales.